Assessing Risky Riding Behaviors Among Food Delivery Motorcyclists in Thailand: Insights from the Motorcycle Rider Behavior Questionnaire and Health Belief Model - Wimon Laphrom; Thanapong Champahom; Chamroeun Se; Supanida Nanthawong; Panuwat Wisutwattanasak; Vatanavongs Ratanavaraha; Sajjakaj Jomnonkwao (Logistics, 2024)
Background: Food delivery motorcyclists face unique risks that often lead to risky riding behaviors. Thailand, with one of the highest rates of motorcycle-related injuries and fatalities globally, has seen a surge in food delivery services following the COVID-19 pandemic, increasing the number of motorcyclists on the roads. Delivery motorcyclists are especially vulnerable due to frequent exposure to traffic congestion, time pressures, and adverse weather. This study aims to identify key health beliefs and external factors contributing to risky riding behaviors among food delivery motorcyclists in Thailand. Methods: The study surveyed 2000 food delivery motorcyclists across five regions in Thailand, employing the Motorcycle Rider Behavior Questionnaire and the Health Belief Model. Structural equation modeling was used to analyze the relationships between health beliefs and risky riding behaviors. Results: The analysis revealed that health motivation, perceived susceptibility, perceived severity, perceived benefits, and cues to action were negatively associated with risky riding behaviors. Conversely, perceived barriers positively influenced these behaviors. Fatigue and aggressive riding were significant predictors of increased risky behaviors at the 0.001 level. Conclusions: Addressing individual health beliefs and external factors like fatigue and aggression is essential for reducing risky riding behaviors and preventing severe injuries.